The perceived deservingness of COVID-19 healthcare in the Netherlands: a conjoint experiment on priority access to intensive care and vaccination - Tim Reeskens; Femke Roosma; Evelien Wanders (BMC, 2021)
Abstract Background Amidst the COVID-19 pandemic, governments, health experts, and ethicists have proposed guidelines about ICU triage and priority access to a vaccine. To increase political legitimacy and accountability, public support is important. This study examines what criteria beyond medical need are deemed important to be perceived of priority COVID-19 healthcare access. Method Two conjoint experiments about priority over ICU treatment and early COVID-19 vaccination were implemented in a probability-based sample of 1461 respondents representative of the Netherlands. Respondents were asked who should receive treatment out of two fictitious healthcare claimants that differed in in age, weight, complying with corona policy measures, and occupation, all randomly assigned. Average marginal coefficient effects are estimated to assess the relative importance of the attributes; attributes were interacted with relevant respondent characteristics to find whether consensus exists in this relative ranking. Results The Dutch penalize those not complying with coronavirus policy measures, and the obese, but prioritize those employed in 'crucial' sectors. For these conditions, there is consensus among the population. For age, young people are prioritized for ICU treatment, while the middle-aged are given priority over a vaccine, with younger respondents favoring healthcare for elderly claimants, while older respondents favor support for young cohorts. Conclusion People who have no control over their social risk and are able to reciprocate to society are considered as more deserving of priority of COVID-19 healthcare. Our findings provide fair support for the implemented ethical guidelines about ICU-treatment and COVID-19 vaccines.